Circulating Cellular Adhesion Molecules and Cognitive Function: The Coronary Artery Risk Development in Young Adults Study - Yoon, Cynthia Yursun; Steffen, Lyn M.; Gross, Myron D.; Launer, Lenore J.; Odegaard, Andrew; Reiner, Alexander; Sanchez, Otto; Yaffe, Kristine; Sidney, Stephen; Jacobs, David R. (Frontiers in Cardiovascular Medicine, 2017)
Objective Higher circulating concentrations of cellular adhesion molecules (CAMs) can be used as markers of endothelial dysfunction. Given that the brain is highly vascularized, we assessed whether endothelial function is associated with cognitive performance. Method Within the Coronary Artery Risk Development in Young Adults (CARDIA) Study, excluding N = 54 with stroke before year 25, we studied CAMs among N = 2,690 black and white men and women in CARDIA year 7 (1992–1993, ages 25–37) and N = 2,848 in CARDIA year 15 (2000–2001, ages 33–45). We included subjects with levels of circulating soluble CAMs measured in year 7 or 15 and cognitive function testing in year 25 (2010–2011, ages 43–55). Using multiple regression analysis, we evaluated the association between CAMs and year 25 cognitive test scores: Rey Auditory Verbal Learning Test (RAVLT, memory), Digit Symbol Substitution Test (DSST, speed of processing), and the Stroop Test (executive function). Result All CAM concentrations were greater in year 15 vs. year 7. Adjusting for age, race, sex, education, smoking, alcohol, diet, physical activity, participants in the fourth vs. the first quartile of CARDIA year 7 of circulating intercellular adhesion molecule-1 (ICAM-1) scored worse on RAVLT, DSST, and Stroop Test (p ≤ 0.05) in CARDIA year 25. Other CAMs showed little association with cognitive test scores. Findings were similar for ICAM-1 assessed at year 15. Adjustment for possibly mediating physical factors attenuated the findings. Conclusion Higher circulating ICAM-1 at average ages 32 and 40 was associated with lower cognitive skills at average age 50. The study is consistent with the hypothesis that endothelial dysfunction is associated with worse short-term memory, speed of processing, and executive function.